Role of Shadow Prices in Economic Analysis: Estimating True Economic Value beyond Market Prices - Nepal, Pramshu (Kalika Journal of Multidisciplinary Research, 2024)
Shadow prices or accounting prices are crucial for accurately valuing factors and products beyond their market prices. They adjust for market distortions, externalities, and other factors to reflect the true social value of goods and services. In cost-benefit analysis, shadow prices are used to evaluate the social profitability of public sector projects by translating market prices into more accurate measures of economic value through conversion factors. Shadow prices, such as shadow wages and shadow exchange rates, fluctuate based on local conditions like unemployment and balance of payments issues. They provide a more realistic view of resource value, particularly important for developing countries. Incorporating shadow prices helps address market failures, improve the accuracy of cost-benefit analyses, and inform policy decisions on subsidies, taxes, and resource management. Despite challenges like data limitations and static assumptions, shadow pricing is vital for optimizing resource allocation and supporting sustainable development by considering broader societal impacts, especially in economies where market distortions are significant.